Marketing Communication Model to Enhance Hotel Brand Image - Anak Agung Ngurah Wira Kusuma; I Nyoman Rajin Aryana; Budi Susanto; Made Sudiarta (The Postgraduate School of Tourism Sahid Polytechnic, 2022)
ABSTRACT Purpose: The purpose of this study was to determine the position of the marketing communication model implemented to improve the brand image of The Kayon Jungle Resort, Bali, Indonesia, and to determine the alternative marketing communication model that should be applied by the Sales and Marketing Department in improving the brand image of the hotel. Research methods: The analytical technique used is the mixed method design of Sequential Exploratory; Internal Factor Summary Matrix (IFAS), External Factor Analysis Summary Matrix (EFAS), Internal-External Matrix (IE), SWOT Analysis, and Quantitative Strategic Planning Matrix (QSPM). Results and discussion: The results of the IFAS matrix analysis show that the main strengths are reviews and comments left by guests on the internet, as well as having a distinctive and unique room, restaurant, swimming pool, yoga pavilion, and gym, while the main weaknesses are a lack of variety and intensity of sales promotion activity. According to the results of the EFAS matrix analysis, the main opportunity is the Policy to maintain guest privacy, safety, and comfort by The Kayon Jungle Resort management, while the main threat is the Intensity of beneficially campaign. Implication: The Kayon Jungle Resort is in the Growth Strategy (Cell I) position according to the results of the IE matrix analysis. The SWOT analysis results in nine alternative marketing communication strategies, three of which are prioritized and calculated by the QSPM matrix with a total TAS of 303.72, 298.05, and 287.31. Keywords: marketing communication, alternative strategy, brand image.